ANALYSIS LONG-TERM DEBT AND CURRENT RATIO TO FIRM VALUE IN CONSUMPTION COMPANIES - Efriyenty, Dian (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
Book Value in the manufacturing sector fluctuated in 2015-2019. The decline in the value of CR has an impact on investors' interest in investing and interest in buying shares. The purpose of this study is to analyze long-term debt and current ratio to firm value. This research is conducted on a consortium of 9 companies. Analysis method used partial test and testing simultaneously. The results of research on long-term debt do not have an impact on the value of the company which has a value of 0.598 above 0.05, while the current ratio has an impact on firm value, which is a value of 0.532 over 0.05. And at the same time, long-term debt and current ratio have an impact on firm value with a value of 0.030 less than 0.05.